"Think" Pragmatically: Children's Interpretation of Belief Reports. Issue 4 (2nd October 2017) - Lewis, Shevaun; Hacquard, Valentine; Lidz, Jeffrey
ABSTRACT: Children under 4 years of age often evaluate belief reports based on reality instead of beliefs. They tend to reject sentences like, "John thinks that giraffes have stripes" on the grounds that giraffes do not have stripes. Previous accounts have proposed that such judgments reflect immature Theory of Mind or immature syntactic/semantic representations. We argue that the difficulty is actually pragmatic. Adults frequently use belief reports to provide information about reality (e.g., "I think the stove is still hot"). Young children have difficulty determining when the main point is reality (the stove situation) vs. mental states (John's ideas about giraffes). We show that if the context emphasizes beliefs, children are more able to evaluate belief reports appropriately (Experiment 1). The pattern of children's truth value judgments demonstrates that they understand the literal meaning of think sentences, despite their pragmatic difficulty grasping the speaker's intention (Experiment 2).